(untitled) (Research, Society and Development, 2021)
The tranexamic acid is a substance that inhibits the action of plasminogen, which normally binds to clots to destroy them. However, in people with systemic diseases, plasminogen can also prevent clots from forming, making it difficult to stop bleeding. Its therapeutic formulations include tablet, gel or injectable forms to correct or prevent emergencies related to excessive bleeding, thus being an effective agent for local hemostasis in invasive dental procedures. This study aims to demonstrate the current use of tranexamic acid in various dental procedures, highlighting its effectiveness in the clinical and surgical process. This is an integrative bibliographic review conducted through a bibliographic survey in the main electronic databases, SciELO, LILACS, MEDLINE and BBO consulting the available literature from 2009 to 2019. Immediate treatment with tranexamic acid was found to reduce the risk of death by 70% in people with severe bleeding. However, early treatment is important because even small delays are associated with reductions in benefit. Tranexamic acid is indicated primarily to reduce the risk of bleeding during surgery and to treat bleeding associated with excessive fibrinolysis, and is safe and effective in the dental procedures of systemically compromised patients, such as minor oral surgeries, periimplant bone repairs, implants. dentistry, management of cystic lesions and subgingival scraping, among others.